Game Models in Improving Volleyball Bottom Passing Results - Muhammad Abdul Aziz Aziz; Dewi Susilawati; Entan Saptani (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research aims to find out whether there is an influence of game models on the results of bottom passing in volleyball. This research method is quantitative with an experimental approach with a research design using a pre-test-post-test one-group design. Using a research sample of 30 people, it can be concluded that the meaning of Underpass is one of the basic techniques in the game of volleyball which is a player's attempt to pass the ball to a teammate using both wrists together, hitting the ball right in the middle of the calculation. in the Shapiro-Wilk column, the significance value obtained in the individual pretest was 0.332 > 0.05, while the group model posttest was 0.050 > 0.5. Based on these values, it can be concluded that the data distribution is normal. So Ha is accepted and Ho is rejected. So it can be said that the T-test has a significant influence, namely game models, on the results of bottom passing ability.